INNOVATIVE INFRASTRUCTURE DEVELOPMENT AND SUSTAINABLE INDUSTRIALIZATION - Lesik, I. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article examines the essence, preconditions of formation and development of innovative infrastructure on the course to sustainable industrialization. The author considers the modern tendencies of technological infrastructure development of Ukraine. Such tendencies while globalization demand radical transformations for overcoming of economic backwardness that step up the country on the new level of industrialization. We comparatively evaluated development tendencies of innovative infrastructure using «Global Competitiveness Index», «Global Innovation Index» and several other indicators, demonstrated the resource potential of the country and explained its position in the world ranking. We outlined the shortcomings and risks associated with urbanization, environmental pollution, limited resources, etc. The article shows the causal link between political, institutional, socio-economic, environmental and other factors on the road to sustainable industrialization. It has been proved that the main priorities of each country in defining the strategy of infrastructure development and sustainable industrialization should be focused on healthy pragmatism and national interests. We investigated that the optimization of the taxational load; observance of a certain proportion between sectors of the national economy; decentralization of power; improvement of antimonopoly policy; development of an effective policy request to reduce anthropogenic load; use of alternative energy; training and retraining of staff and many other aspects requires intensified attention. These aspects are the constitute of an integrated approach to the implementation of strategic orientations for competitiveness, innovation and sustainable development.